Community-Based Collaborative Management: Impacts and Challenges of Sea Turtle Conservation on the South Coast of Central Java, Indonesia - Kartono Kartowijono; Aryuni Yuliantiningsih; Tedi Sudrajat; Baginda Khalid Hidayat Jati (Jurnal Hukum, 2024)
The use of community-based collaborative management has shown promising results in addressing the complex issues surrounding sea turtle conservation. However, the legal implications and barriers associated with this method have not been thoroughly investigated. This study seeks to examine legal policies governing conservation institutions that influence community-based turtle protection along the southern coast of Central Java, Indonesia. The focus of this study is on two specific case studies: a conservation group at Pantai Sodong and another at Pantai Kembar. Employing a qualitative research design, this study incorporated semi-structured interviews with conservation group administrators, government officials, and other relevant stakeholders. Apart from that, this research also involves analysis of legal and regulatory documents and policies which is complemented by field observations. These findings indicate that community-based conservation policies significantly increase legal behavior that is in line with conservation law provisions. However, this report also underscores the legal and institutional challenges faced by local community-based conservation groups. These challenges include the necessity of legal collaboration between community groups and the government, the availability of healthcare facilities such as quarantine centers and clinics, and the need for a permanent workforce with appropriate skills. This study emphasizes the need for more flexible standards regarding conservation institutional requirements and government support to encourage the fulfillment of the validity and legal certainty of conservation institutions. This study adds to the growing body of literature on legal approaches to community-based collaborative management, and offers important insights for policymakers and legal practitioners who wish to increase support for community-based conservation programs in Indonesia and other countries.